Seasonal changes in metabolic rates in muskoxen following twenty- four hours of starvation - Lawler, James P.; White, Robert G. (Rangifer, 1997)
Timing of seasonal trends in post-prandial energy expenditure (EE) was measured in muskoxen (2 males and 1 female) given a standardized meal followed by a 24-26 h starvation during 10 months over the course of a year. EE was significantly lower in winter than summer. CH4 production (EctM) was reversed with winter highs and summer lows. Ratio of ECH4:EE indicates a change in dietary efficiency but this difference was not associated with a seasonal shift in RQ which was constant. The main increase in EE from winter to summer occurred between April and May and the summer to winter decrease between August and Septembet.
Keywords: Muskoxen; metabolic rates; Ovibos moschatus; energy expenditure; seasonality; methane